Study the potential role of IL-17 in Toxoplasmosis prevalence in SLE patients (Texas Journal of Agriculture and Biological Sciences, 2022)
Toxoplasma gondii is an opportunistic pathogen that can kill congenitally infected fetuses, newborns, and immunocompromised patients by reactivating a latent infection. The aim of study knowing the extent of Toxoplasma effect of on the level of IL-17 in SLE patient. In this study, 250 blood samples from both genders female and male were collected. Using the ELISA technique, T. gondii immunoglobulins (IgG and IgM) antibodies and (IL-17) levels were assessed in all serum samples. According to the findings of this investigation, SLE patients had the greatest rate of toxoplasmosis infection. The percentage of anti-Toxoplasma IgG (50%) was higher than the percentage of anti-Toxoplasma IgM (4%), across all groups. IL-17 was highly in SLE and Toxoplasma infected patient (151.87 ± 5.99). These result is suggested that direct pro-inflammatory activity, may have a role in SLE pathogenesis. Toxoplasmosis must be diagnosed and treated in SLE patients in order to lessen the impact of the illness because most immunocompromised people are exposed to a number of possible risk factors, including Toxoplasma original infection or reactivation